O1-S04.01 Increasing adolescent HIV prevalence in Northeastern Zimbabwe: evidence of long-term survivors of mother to child transmission. (10th July 2011) - Eaton, J; Takavarasha, F; Gregson, S; Hallett, T; Mason, P; Robertson, L; Schumacher, C; Nyamukapa, C; Garnett, G
Abstract : Background: Longitudinal data from eastern Zimbabwe suggested an increase in HIV prevalence among 15 to 17 year olds between 2005 and 2008. Prevalence increased from 1.2% to 2.6% among adolescent males and from 2.2% to 2.8% in females (see Abstract O1-S04.01 figure 1 ). This is surprising given a general trend of decreasing HIV prevalence in the past decade associated with a reduction in sexual risk behaviour. It is unknown whether the increase is the result of resurgence in risky sexual behaviour, or long-term survival of infants infected perinatally during the early 1990s when prevalence was increasing exponentially among pregnant women in Zimbabwe Methods: We use data from the Manicaland HIV/STD Prevention Project collected between 2006 and 2008 to test hypotheses indicating whether adolescent HIV infections are likely sexually acquired or perinatally acquired. We use Fisher's exact test and relative risk regression to examine the association between adolescent HIV infection and (i) maternal mortality, (ii) adolescent sexual behaviour, and (iii) chronic illness. Results: There were 990 males and 972 females aged 15 to 17 years included in the cohort. Mothers of HIV positive adolescent males were more likely to be deceased than those of HIV negative males (RR 2.72, p <0.001). Mothers of HIV positive females were not more likely to be deceased, but were more likely to be HIV positive if still alive (RR 3.68, p <0.001). Among males there was no association between having had sex and HIV status. Sexually active females were more likely to be HIV positive (RR 2.44, p =0.042). During the period that adolescent prevalence increased, the proportion of adolescent males who reported having had sex reduced from 14% to 8% (p <0.001), and did not change in females. HIV positive adolescents were more likely to report recurring sickness or chronic illness, indicative of late-stage HIV infection. Conclusions: Increasing HIV prevalence in adolescent males cannot be explained by a rebound in sexual risk behaviour and is likely attributable to long-term survivors of perinatal HIV transmission. Among females, both perinatal and sexual transmission account for adolescent HIV infections. These findings question the interpretation of HIV prevalence in young people as an indicator of recent trends in HIV incidence. They suggest an urgent need to prevent onward HIV transmissions by perinatally infected adolescents and the expansion of HIV testing and treatment to include young people.